The date of the ‘Rule of the Four Fathers’ and the beginnings of the Monastery of Lérins - Figuinha, Matheus Coutinho (Romanitas - Revista de Estudos Grecolatinos, 2015)
The monastery of Lérins, founded by Honoratus between 400 and 410, was the most important monastic institution of the West during the fifth century. Adalbert de Vogüé and Jean-Pierre Weiss have recently engaged in a complex discussion regarding the first rule of the monastery, the so-called Rule of the Four Fathers. In this paper, I reconsider both scholars’ arguments and investigate when and why the Rule of the Four Fathers was composed. I suggest that Honoratus and his first companions established themselves in Lérins as hermits and that the Rule of the Four Fathers was written between 414 and 419 in order to legitimate the consolidation of the Lerinian hermits under a single monastery and the superior’s authority.
Keywords: Late Antiquity; Monasticism; Lérins; Rule of the Four Fathers